Putrescine as indicator of manganese neurotoxicity: Dose-response study in human SH-SY5Y cells. (June 2018) - Fernandes, Jolyn; Chandler, Joshua D.; Liu, Ken H.; Uppal, Karan; Go, Young-Mi; Jones, Dean P.
Abstract: Disrupted polyamine metabolism with elevated putrescine is associated with neuronal dysfunction. Manganese (Mn) is an essential nutrient that causes neurotoxicity in excess, but methods to evaluate biochemical responses to high Mn are limited. No information is available on dose-response effects of Mn on putrescine abundance and related polyamine metabolism. The present research was to test the hypothesis that Mn causes putrescine accumulation over a physiologically adequate to toxic concentration range in a neuronal cell line. We used human SH-SY5Y neuroblastoma cells treated with MnCl2 under conditions that resulted in cell death or no cell death after 48 h. Putrescine and other metabolites were analyzed by liquid chromatography-ultra high-resolution mass spectrometry. Putrescine-related pathway changes were identified with metabolome-wide association study (MWAS). Results show that Mn caused a dose-dependent increase in putrescine over a non-toxic to toxic concentration range. MWAS of putrescine showed positive correlations with the polyamine metabolite N8-acetylspermidine, methionine-related precursors, and arginine-associated urea cycle metabolites, while putrescine was negatively correlated with γ-aminobutyric acid (GABA)-related and succinate-related metabolites ( P  < 0.001, FDR < 0.01). These data suggest that measurement of putrescine and correlated metabolites may be useful to study effects of Mn intake in the high adequate to UL range. Highlights: Manganese (Mn) has narrow margin between adequate intake (AI) and tolerable upper intake level (UL), causing neurotoxicity in excess. Putrescine is elevated in neurologic disorder and neurotoxicity. Dosing in neuroblastoma cells to give normal to toxic human brain Mn levels caused dose-dependent increase in putrescine. Changes in polyamines, urea cycle and methionine metabolites correlated with putrescine. Putrescine and related metabolites may provide basis to study and evaluate Mn intake as contributor to neurologic disorders.